The Role of Rain Forecasting in Flood Risk Reduction, Case Study of Kigali City, Rwanda - Niyomugabo, Desire; Nkezabera, Jean Adolphe; Maniragaba, Abias; Bizimana, Jean Paul; Nahayo, Lamek; Nduwimana, Onesphore (International Journal of Climate Research, 2022)
Floods are recognized as a severe natural disaster influenced potentially by anthropogenic activities. Kigali downstream floods were coming from the drainage system and the flow of streams. The study revealed on contribution of rain forecasting in reduction of flood risk in Kigali city, to show how well forecasted rain used to decrease flood risk among urban residents. The objectives were to carry out a flood risk analysis, determining the potential frequencies rainfall occurred and assessing the contribution of rain forecasting on flood risk reduction. The data was for Kigali city in three districts (Nyarugenge, Gasabo and Kicukiro) from 2016 to 2020, collected from literature review on disaster in Kigali city and Statistical package for social sciences (SPSS) tool and Microsoft excel was used in analysis. The risk analysis factors were based on deaths, injury, infrastructure loss and crops loss per ha, the prone district is Nyarugenge. The Pearson correlation coefficient between variables mostly had positive correlation and in significate range with flood risks in both districts but on different range with such exception of negative relationship. Nyarugenge district precipitation made positive correlation with infrastructure and deaths, r= 0.138 in range 0<r< 0.25 very low correction; r=0.673 in range 0.50≤r<0.75 high correlation, respectively conclude that the increase of precipitation led to raise both infrastructure loss and deaths. Recommended measures will base on particular features of district (soil type, land use, geology and geomorphology analysis) especially on Nyarugenge district, which is more suspended to the floods to mitigate and adapt flood risks.